Rhizosphere domestication enhances root colonization and plant growth promotion performance of Bacillus velezensis SQR9 - Wang, Zhengqi; Zhao, Yike; Shao, Jiahui; Wang, Jingjing; Xun, Weibing; Sun, Xinli; Xu, Zhihui; Miao, Youzhi; Huang, Guidong; Liu, Derui; Zhang, Ruifu; Shen, Qirong; et al. (Frontiers in Microbiology, 2025)
The overuse of chemical fertilizers has caused severe soil degradation and environmental pollution, necessitating sustainable alternatives such as microbial fertilizers containing plant growth-promoting rhizobacteria (PGPR). However, application of laboratory-developed microbial inoculants usually reveals impaired performance, attributing to complicated field conditions including plant genotype, soil property, and interaction with indigenous microbiota. Currently, traditional microbial breeding methods such as random mutagenesis and genetic engineering, could not be so appropriate for screening agents with comprehensive phenotypes (e.g., root colonization and plant growth-promotion effects). In the present study, we developed a rhizosphere domestication strategy for PGPR strain Bacillus velezensis SQR9, involving 20 cycles (approximately 160 generations in total) of in situ transfer and evolution in pepper rhizosphere. Evolved strains achieved 1.5 ~ 2.9-fold greater root colonization than the ancestral strain. A three-step phenotypic screening of 45 evolved strains firstly identified 29 candidates showing enhanced indole-3-acetic acid (IAA) production, biofilm formation, or siderophore production compared to the ancestor. Subsequent screening picked 6 strains with superior plant growth-promoting effects than the ancestor in hydroponic system. Final pot experiment confirmed the evolved strain 9P41 as the optimal performer, of which the inoculated pepper plants exhibiting 11.4% greater height, 28.7% longer roots, 21.0% higher aboveground biomass, and 29.1% increased underground biomass compared to plants treated with the ancestor. Genomic resequencing identified adaptive mutations in mlnD, smc, and fhuC genes are potentially associated with phenotypic improvements of strain 9P41. This rhizosphere adapted domestication strategy successfully breed evolved strains with improved plant growth-promoting efficacy, providing a novel solution for developing microbial inoculants and biofertilizers needed in sustainable agriculture.